2021
DOI: 10.1186/s42269-021-00581-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination and coexistence of metal and antibiotic resistance in Vibrio species recovered from aquaculture ponds with and without history of antibiotic usage in Southwest Nigeria

Abstract: Background The use of metal-containing and antimicrobial compounds is a common practice in aquaculture operations in Nigeria. Only a few studies have focused on the impact of these chemicals on metal and antibiotic resistance development in the bacterial flora of aquaculture. This study therefore sets out to fill this gap. Results Five metals, namely copper (Cu), zinc (Zn), lead (Pb), nickel (Ni) and chromium (Cr), were detected at different conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The highest rates of resistance in this study were observed against two beta-lactam antibiotics, augmentin (67.7%) and cefuroxime (68.8%). This rate was slightly higher than observed in a 2021 study (Adekanmbi et al, 2021) which reported a 44.3% resistance. Other studies simply tested against ampicillin and reported rates ranging from 76.92% to 94.1% (Islam et al, 2021;Gxalo et al, 2021).…”
Section: Discussioncontrasting
confidence: 62%
“…The highest rates of resistance in this study were observed against two beta-lactam antibiotics, augmentin (67.7%) and cefuroxime (68.8%). This rate was slightly higher than observed in a 2021 study (Adekanmbi et al, 2021) which reported a 44.3% resistance. Other studies simply tested against ampicillin and reported rates ranging from 76.92% to 94.1% (Islam et al, 2021;Gxalo et al, 2021).…”
Section: Discussioncontrasting
confidence: 62%
“…The El Tor strains compare to the classical strains are more adapted and resilient to the environment, cause a higher infection-to-case ratio and have more asymptomatic carriers [95,126]. Some studies have reported low resistance of the SA-NAG V. cholerae against amoxicillin/clavulanate [117,127,128] however, other studies like ours have shown that different V. cholerae serotypes can exhibit high resistance against amoxicillin/clavulanate [129,130].…”
Section: Plos Onementioning
confidence: 80%
“…cholerae against amoxicillin/clavulanate [ 117 , 127 , 128 ] however, other studies like ours have shown that different V . cholerae serotypes can exhibit high resistance against amoxicillin/clavulanate [ 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Di-Cesare et al [ 42 ] reported co-selection of bacteria isolated from freshwater at Lake Orta, Italy to heavy metals and antibiotics. Adekanmbi et al [ 43 ] also reported co-existence of resistance to metals and antibiotics in Vibrio species isolated from fish ponds with and without antibiotics usage history. This observation is a major cause of concern for public health since illnesses caused by multidrug-resistant bacteria are difficult to treat and should they possess genes conferring such resistance, they may be transferred by different means to other bacteria present in their immediate environment, thereby conferring resistance to many classes of antibiotics as well.…”
Section: Discussionmentioning
confidence: 99%